One Occurrence of the Symbolic Reception of "The Man in the Panther’s Skin" - Lomidze, Kote (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2022)
As a result of the reconstruction of Valerian Gaprindashvili's theoretical views and the analysis of poetic works, it was outlined that V. Gaprindashvili intends to create a myth on Rustaveli. He discusses Rustaveli's literary work as the work with the aspects characteristic of modernism. He understands "The man in the panther skin" according to two origins of the creativity given by Nietzsche and attributes the poem to a series of Apollonian works. Via allusion of chivalry novels the poet links Avtandili to the heroes of courtesy novels. Reception of Avtandili’s image is also original – Avtandili perceived as the knight self-sacrificed to a friend, is conceived as an enamored character in "Rain performance".